„Ex mellifluis verbis”: Martin von Cochem (Linius, 1634–1712) imádságoskönyve magyarul (1681) - Knapp, Éva (Studia Litteraria, 2013)
Martin von Cochem (born as Martin Linius) was a dominant figure of 17th and18th century Central-European prayer literature and devotional prose. To my knowledge, research on his literary activity in Hungary has so far been limited to one work only: Makula nélkül való tükör [A Mirror free from Mortal Taint] (first Hungarian edition: Nagyszombat/Trnava, 1712). The oeuvre of this Capuchin monk, who became a best-seller author of his time, consists of thirty-four basic works and their serial editions had stayed continuously in print with different titles until the 1950s. His life-work has largely influenced the genres and the theoretical framework of early modern Hungarian devotional literature. The Hungarian edition of Martin von Cochem’s prayer book entitled Mennyei követek avagy Sz. Gertrudis és Mechtildis égböl vött imádsági [Heavenly Messengers or Celestial Prayers of Saints Gertrude and Mechtilde] (1681), followed the Latin and the German editions ten years later (Preces Gertrudianae). My paper points out the changes both in the structure and content of the Hungarian translation. This work is known with six Latin and German title variations. Previous research has already identified more than fifty editions. I add nearly forty new editions to this corpus, existing under three different Hungarian titles (Mennyei követek [Heavenly Messengers], Len kötelecske [Flax Rope], Az két atyafi szent szüzek Gertrudis és Mechtildis imádságos könyve [Prayer Book of the Two Saint Virgins, Gertrude and Mechtilde]), and I also touch upon the approximately two hundred year-long reception history of this work in Hungary.